Pengembangan Modul Ajar Melakukan Instalasi Perangkat Jaringan Lokal Untuk Siswa Kelas XI Program Keahlian Teknik Komputer Dan Jaringan (TKJ) Di Smk Negeri 3 Tabanan - Wira Adnyana, I Putu; Sugihartini, Nyoman; Windu Antara Kesiman, Made; Seri Wahyuni, Dessy (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2014)
This research aimed to (1) design and implement the learning module of Conducting the Installation of Local Area Network for the students of class XI of computer and network program at SMK Negeri 3 Tabanan. (2) To know the responses of the students of class XI of computer and network program at SMK Negeri 3 Tabanan toward the development of the learning module of Conducting the Installation of Local Area Network. This research was a Research and Development research by using the development model of Dick and Carey. This research involved the students of class XI of computer and network program at SMK Negeri 3 Tabanan in academic year 2013/2014. The development of the learning module of Conducting the Installation of Local Area Network used phases of draft development. The responses of the students toward the learning module were gained by using questionnaire. The result of data analysis of students’ responses show that the percentage of the students who give the extremely positive responses are 87.71%, the percentage of the students who give the positive responses are 14.29%, and there are no students who give less positive, negative and extremely negative responses. The mean score of students’ responses is 63.67. The mean score show that the responses of the students toward the development of learning module of Conducting the Installation of Local Area Network are categorized as extremely positive.